Driving MSME Competitiveness in Kediri through Innovation, Digital Marketing, and Standardized Financial Reporting - De Fara, Florenchia Della; Andy Chandra Pramana; Gandung Satriyono (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the influence of product innovation, digital marketing strategies, and the quality of financial reporting based on SAK EMKM on the competitiveness of MSMEs in Kediri City. Using a quantitative approach with explanatory research design, data were collected through questionnaires from MSME actors. The results of the analysis show that product innovation, digital marketing strategies, and the quality of financial reporting do not have a significant individual effect on the competitiveness of MSMEs. These findings indicate that the relationship between these three variables and competitiveness is more complex than a simple direct influence. The insignificant results suggest that for MSMEs in Kediri City, these factors may function as basic capabilities that require complementary strategies such as effective commercialization, advanced digital engagement, and a supportive financial ecosystem to be effectively translated into competitive advantage. This study emphasizes the need for an integrated approach in MSME development, where innovation, digitalization, and financial formalization are synergized within a comprehensive support framework. The findings provide important implications for MSME actors, policymakers, and supporting institutions in designing more effective interventions to improve the competitiveness of local MSMEs.